2015
DOI: 10.14475/kjhpc.2015.18.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Care Stress, Job Satisfaction and Terminal Care Performance for Nurses in Internal Medicine Wards

Abstract: This study is aimed to investigate the relationship among terminal care stress, job satisfaction and terminal care performance nurses in internal medicine wards and to provide a basis to improve terminal care performance. Methods: This is a descriptive study performed with 201 nurses who have at least one year of experience and are stationed at the internal medicine department of three general hospitals and three university hospitals in P city of a metropolitan city B. The nurses also had an experience with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Cancer is known to cause death following diagnosis and threaten a person's physical, social, and spiritual well-being. End-of-life is that part of life where a person is living with, and impaired by an eventually fatal condition, even if the prognosis is ambiguous or unknown [3,4]. End-of-life care combines the broad set of health and community services that care for the population at the end of their lives [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer is known to cause death following diagnosis and threaten a person's physical, social, and spiritual well-being. End-of-life is that part of life where a person is living with, and impaired by an eventually fatal condition, even if the prognosis is ambiguous or unknown [3,4]. End-of-life care combines the broad set of health and community services that care for the population at the end of their lives [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Thematic analysis of care at the end-of-life identified six main topics of interest, namely, uncertainty of treatment for patients at end-of-life, quality of life issues, costs, ethical and social issues, interaction between medical staff and other services, and strategies for out-of-hospital care [3]. Nurses who provide end-of-life care directly face internal problems and experience higher stress as a result of the excessive expectations of patients or caregivers regarding the progress of cancer treatment, repeated ideals, and disappointments in reality [4][5][6]. If the nurses providing end-of-life care do not have enough time to recharge due to the accumulation of physical and psychological stress, their health and well-being in daily life are impaired [4,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 임종간호 스트레스 (7,(17)(18)(19), 임종간호수행에 미치는 영향 (8,16,19) No knowledge and skills to provide end-of-life care.…”
unclassified
“…Since most nurses do not have a clear understanding of death, it has been reported that they feel frustration, sadness, fear, and pressure when they have to care for dying patients [ 7 - 9 ]. Sasahara et al [ 10 ] found that most nurses experienced difficulties in providing care for dying patients and did not have much knowledge about coping with death or dying.…”
Section: Introductionmentioning
confidence: 99%